First‐in‐human orbital tumor surgery guided by near‐infrared II window fluorescence imaging: A feasibility study - Zeyu Zhang; Lishuang Guo; Lan Yao; Yueyue Li; Yan Hei; Qi Wang; Xiaoyi Wang; Rui Ma; Xinji Yang; Zhenhua Hu; Wei Wu (Interdisciplinary Medicine)
Abstract Precise resection of orbital tumors is a critically important but elusive issue. Fluorescence imaging in the near‐infrared II window (NIR‐II) holds the potential to provide the surgeons with real‐time identification for orbital tumors. Here, for the first time, we evaluated the feasibility and clinical value of NIR‐II fluorescence imaging in orbital tumor surgery. To establish the method of NIR‐II fluorescence imaging for orbital tumors, we developed a NIR‐II fluorescence imaging system and indocyanine green (ICG) served as the fluorescent contrast agent. Twenty‐two patients diagnosed with orbital tumors and scheduled for standard‐of‐care surgery were enrolled in this study. Time‐course NIR‐II fluorescence imaging of two patients with superficial orbital tumors showed the optimum imaging time was 2 h post injection of ICG. Fifteen patients were allocated for diagnostic test, which showed that both the in situ and ex vivo NIR‐II fluorescence imaging showed better sensitivity and specificity than the surgeon judgment. In the feasibility trial of the remaining five patients, the surgeon encountered 34 suspicious regions and surgical decisions were changed nine times due to NIR‐II fluorescence imaging. The resultant seven additional resections were justified by histopathology and the two conservative treatments did not result in recurrence. Based on these findings, we suggested that ICG‐based NIR‐II fluorescence imaging was feasible to guide precise resection of orbital tumors. A future randomized controlled trial with a larger cohort is encouraged to further verify the clinical value.